Potential of adsorbents from agricultural wastes as alternative fillers in mixed matrix membrane for gas separation: A review - Alia Aqilah, Ghazali; Sunarti, Abd Rahman; Rozaimi, Abu Samah (Walter de Gruyter GmbH, 2020)
Mixed matrix membrane (MMM), formed by dispersing fillers in polymer matrix, has attracted researchers’ attention due to its outstanding performance compared to polymeric membrane. However, its widespread use is limited due to high cost of the commercial filler which leads to the studies on alternative low-cost fillers. Recent works have focused on utilizing agricultural wastes as potential fillers in fabricating MMM. A membrane with good permeability and selectivity was able to be prepared at low cost. The objective of this review article is to compile all the available information on the potential agricultural wastes as fillers in fabricating MMM for gas separation application. The gas permeation mechanisms through polymeric and MMM as well as the chemical and physical properties of the agricultural waste fillers were also reviewed. Additionally, the economic study and future direction of MMM development especially in gas separation field were discussed.